Immune Response after Covid 19 Vaccination as an effort to prevent infection and Herd Immunity - Kusbaryanto, Kusbaryanto (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2023)
Vaccination programs are one of the most cost-effective and efficient medical therapies in history. This study aims to elicit an immune response after the COVID-19 vaccination and the occurrence of herd immunity. This research is a literature review research by conducting journal searches carried out with the keys: immune response to Covid 19, Covid 19 Vaccination and Herd Immunity. Articles are collected using search engines such as google pubmed, schooler, EBSCO, Sciencedirect, and Proquest. The criteria for the articles used are those published in 2020 – 20232. The Covid 19 virus is a member of the Sarbecovirus subgenus and is distinguished by a stick-shaped spike protein that protrudes from the virion's surface. Global immunization initiatives boost immune systems. Immune cells and proteins that circulate in the body have the ability to provide protection from illness. Prior to immunization, antibodies from patients who had already been exposed to the virus resembled those produced following the first vaccination in healthy individuals. In people who were previously infected after the first vaccination, the level is the same as in people who were not infected after the second vaccination, booster administration has been shown to increase immunity with a 1.5 to 2-fold increase in titers and herd immunity is the only way to end the Covid 19 pandemic.